Partnerstwo w samorządowej polityce oświatowej - Przyszczypkowski, Kazimierz; Cytlak, Izabela (Wydawnictwo Naukowe UAM, 2013)
Analysis of the various documents of the local self-government education indicates that we deal with the evolution of activities concerning the importance of education. At the beginning of the transition period (1990s), local governments indicated mainly fi nancial diffi culties in acquiring education. Thinking about education only in terms of government responsibility was predominant. The main threat to self-government education was then and is now a tendency to unifi cation. One the one hand, it expresses itself by being obedient to the directives and guidelines of the Ministry of Education, on the other hand, in thinking about education in electoral terms. Therefore the focus on short-term spectacular and low-risk activities that do not cause social confl icts. A long-term perspective is slowly but steadily more and more present in local government educational policy in recent (3-4) years. We can observe a clear diversifi cation of activities in the field of financial regulation on self-government education. There is also a growing awareness of the need for financially supporting the education of local extra-budgetary funds (so-called EU funds). The widely promoted idea of an education partnership is an import task for self-government education. This idea may be the basis for connecting current educational issues in local communities with long-term problems. Even though the Polish school continues to be “an isolated island”, it becomes more and more a self-government, community-based school but not in all areas of its functioning.
Partnership in local government educational policy
Keywords: educational policy; educational partnership; local government